Solution-Focused Therapy for improving spouse’s communication pattern - Ramadhana, Firgineta Salsabela; Pertiwi, Ratih Eka; Suryaningrum, Cahyaning (Universitas Muhammadiyah Malang, 2024)
Problems in the family, especially among married couples, are often caused by unhealthy communication patterns such as indirect communication. The aim of this research is to improve communication patterns between husband and wife to be more effective. The assessment was applied to the married couple using interviews, observation methods, and the Couple Communication Satisfaction Scale (CCSS). The results show that the husband and the wife had difﬁculties in expressing their aspirations and emotions. The husband is unable to communicate his loneliness after retirement. Moreover, he wants to spend time with his wife at home. On the other hand, the wife is busy with her work, she rarely pays attention to her husband at home. The intervention technique was 6 sessions of Solution-Focused Therapy (SFT) to improve the communication pattern between spouses. The results indicated that the therapy is an effective intervention to improve communication patterns. At the end of the intervention, the husband and wife can communicate directly and openly. Permasalahan dalam keluarga, khususnya pada pasangan suami istri, sering kali disebabkan oleh pola komunikasi yang tidak sehat seperti komunikasi tidak langsung. Tujuan dari penelitian ini adalah untuk memperbaiki pola komunikasi suami istri agar lebih efektif. Asesmen dilakukan pada pasangan suami istri dengan menggunakan metode wawancara, observasi, dan Couple Communication Satisfaction Scale (CCSS). Hasil penelitian menunjukkan bahwa suami istri mengalami kesulitan dalam mengungkapkan aspirasi dan emosi. Suami tidak mampu mengomunikasikan rasa kesepiannya setelah pensiun. Selain itu, ia ingin menghabiskan waktu bersama istri di rumah. Di sisi lain, istri sibuk dengan pekerjaannya, ia jarang memperhatikan suaminya di rumah. Teknik intervensi yang dilakukan adalah Solution-Focused Therapy (SFT) sebanyak 6 sesi untuk memperbaiki pola komunikasi pasangan suami istri. Hasil penelitian menunjukkan bahwa terapi tersebut merupakan intervensi yang efektif untuk memperbaiki pola komunikasi. Di akhir intervensi, suami istri dapat berkomunikasi secara langsung dan terbuka.